Diastereoselective Synthesis of Camptothecin‐like Scaffolds: Construction of a New Class of Pseudo‐natural Products. Issue 13 (3rd March 2023) - Srikanth, Gourishetty; Ravi, Anil; Sebastian, Anusha; Joseph, Jobi; Khanfar, Monther A.; El‐Gamal, Mohammed I.; Al‐Qawasmeh, Raed A.; Shehadi, Ihsan A.; McN. Sieburth, Scott; Abu‐Yousef, Imad A.; Majdalawieh, Amin F.; Al‐Tel, Taleb H.
Abstract: The discovery of novel small molecules endowed with high 3D‐content remains a powerful tool for interrogating underrepresented biological space. To this end, the pseudo‐natural products (pseudo‐NP) strategy has become one of the most important tools to deliver biologically significant chemical probes. In this article, we describe the development of a new class of pseudo‐NP collection, through connecting tryptamines with a furanose derivative followed by subjecting the product from this operation to a ring distortion strategy that led to diastereoselective synthesis of camptothecin‐like compounds. This process is driven by a cascade that unites Pictet–Spengler reaction with Michael addition reaction, followed by oxidative‐ring enlargement and subsequent transannular aldol cyclization delivering camptothecin‐like architectures. The obtained diastereoselectivity was verified using density functional theory (DFT) calculations. Abstract : Pseudo‐natural products (pseudo‐NP) strategy has become one of the most important tools to deliver biologically significant chemical probes. In this article, we describe the development of a new class of pseudo‐NP collection that led to the synthesis of camptothecin‐like analogues. This process is driven by a cascade that unites Pictet–Spengler reaction with Michael addition reaction, followed by oxidative‐ring enlargement and subsequent transannular aldol cyclization delivering camptothecin‐like architectures.